METHODOLOGICAL PROPOSAL FOR QUALITATIVE RESEARCH IN SEMIOLOGY: ADVANCED STUDIES - Varricchio, Marcia Cristina Braga Nunes; Branco, Morgana Teixeira Lima Castelo; da Silva, Simone; dos Santos Pyrrho, Alexandre; Giorgi, Mario Sergio; de Noronha Gomes, Nelson Bretas; Bolognani, Fabio de Almeida; Gaspar, Sandra Ávila; Nagamatsu, Denise; Braga, Priscila Breder; da Silva, André Vinicius Wendling; da Silva, Jaqueline (Seven Editora, 2025)
Ethical clinical research is complex in its design, requires authorization from the Research Ethics Committee, and sometimes fails to achieve the expected value and recognition, given all the methodological effort involved. Such difficulties also arise in phytotherapy and homeopathy. This group of researchers, specializing in plant extracts and natural products predominantly of Brazilian origin, as well as ultra-diluted and dynamized solutions, relies on the participation of prescribing clinicians who opt for well-designed and consistent case series studies. For thirty years, methodologically organized observations in semiology have been developed, submitted to peers, and published. However, after encountering qualitative research methods, it became clear the potential for combining these methods to strengthen the investigations cited in this article, as they are capable of conferring greater consistency and value to the unique information collected through individual anamnesis and to the specific information identified through physical and complementary examinations, as well as to the spontaneously provided ethnobotanical information. The desire arose to communicate the possibility of designing a methodologically organized study by combining four qualitative research methodologies already used in a dissertation presented to the Graduate Program in Psychosocial Care at the Institute of Psychiatry of the Federal University of Rio de Janeiro. Adapted methodologies were qualitatively evaluated, enabling the future development of multicenter studies. Progress was made in deepening these generated studies, and then, based on the review of clinical records authorized by the Research Ethics Committee (REC), statistical analyses of the phenomena studied, expected (or unexpected) results, and the potential outcome of clinical participation, a complementary summation of these treatments and interventions. With this construct as a result, we discuss potential necessary assessments, which are urgent for the contemporary post-pandemic period. We recommend attention and critical reading of the methodologies used in clinical articles on homeopathy and phytotherapy, understanding their appropriate perspectives and understanding the aspects in which they need to be improved. Given the worrying predictions from INCA and other health agencies regarding the prevalence and incidence of cancer, new efforts and measures must be added to conventional medicine, aiming at the well-being of the population showing clear signs of having an established or developing cancer.DOI: https://doi.org/10.56238/sevened2025.029-053